Risk factors and early prediction of cardiorenal syndrome type 3 among acute kidney injury patients: a cohort study - Hui Lin; Xiaoyu Guo; Mengzhu Wang; Xiaole Su; Xi Qiao (Renal Failure)
Background Type 3 cardiorenal syndrome (CRS type 3) triggers acute cardiac injury from acute kidney injury (AKI), raising mortality in AKI patients. We aimed to identify risk factors for CRS type 3 and develop a predictive nomogram.Methods In this retrospective study, 805 AKI patients admitted at the Department of Nephrology, Second Hospital of Shanxi Medical University from 1 January 2017, to 31 December 2021, were categorized into a study cohort (406 patients from 2017.1.1-2021.6.30, with 63 CRS type 3 cases) and a validation cohort (126 patients from 1 July 2021 to 31 Dec 2021, with 22 CRS type 3 cases). Risk factors for CRS type 3, identified by logistic regression, informed the construction of a predictive nomogram. Its performance and accuracy were evaluated by the area under the curve (AUC), calibration curve and decision curve analysis, with further validation through a validation cohort.Results The nomogram included 6 risk factors: age (OR = 1.03; 95%CI = 1.009–1.052; p = 0.006), cardiovascular disease (CVD) history (OR = 2.802; 95%CI = 1.193–6.582; p = 0.018), mean artery pressure (MAP) (OR = 1.033; 95%CI = 1.012–1.054; p = 0.002), hemoglobin (OR = 0.973; 95%CI = 0.96-–0.987; p < 0.001), homocysteine (OR = 1.05; 95%CI = 1.03–1.069; p < 0.001), AKI stage [(stage 1: reference), (stage 2: OR = 5.427; 95%CI = 1.781–16.534; p = 0.003), (stage 3: OR = 5.554; 95%CI = 2.234–13.805; p < 0.001)]. The nomogram exhibited excellent predictive performance with an AUC of 0.907 in the study cohort and 0.892 in the validation cohort. Calibration and decision curve analyses upheld its accuracy and clinical utility.Conclusions We developed a nomogram predicting CRS type 3 in AKI patients, incorporating 6 risk factors: age, CVD history, MAP, hemoglobin, homocysteine, and AKI stage, enhancing early risk identification and patient management.